2015
DOI: 10.1016/j.jvs.2014.08.112
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of the proximal radial artery arteriovenous fistula

Abstract: The PRAAVF presented low to moderate primary failure and high primary and secondary patency rates with acceptable complications. Consideration of the specific fistula is required when creating a vascular access, especially when a wrist fistula has failed or is predicted to be unsuccessful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 37 publications
1
40
0
3
Order By: Relevance
“…As we have already pointed out, risk of steal syndrome is higher in the AVFs that originate from brachial artery when compared to AVFs that originate from radial artery. With the aim of avoiding the complications, proximal radial artery was used as the inflow artery by various authors (14,15). The major disadvantage of radiocephalic AVFs is the lower blood flow rate (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have already pointed out, risk of steal syndrome is higher in the AVFs that originate from brachial artery when compared to AVFs that originate from radial artery. With the aim of avoiding the complications, proximal radial artery was used as the inflow artery by various authors (14,15). The major disadvantage of radiocephalic AVFs is the lower blood flow rate (1).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was subsequently performed by different techniques by many authors (9)(10)(11)(12)(13). Especially with the aim of avoiding the complications such as steal syndrome, proximal radial artery was used by many surgeons (14,15). In this study, we aimed to report the results of the AVFs that were performed with radiobasilic transposition arteriovenous fistula (RBAVF) technique that originated from the proximal radial artery.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our approach although not equivalent, is comparable to the next available autogenous options using the proximal radial artery. In a recent meta‐analysis of studies describing the proximal radial artery arteriovenous fistula, primary patency and secondary rates were 73.6%, 70.5%, and 80%, 73.7% after 1 and 2 years, respectively …”
Section: Discussionmentioning
confidence: 99%
“…However, plenty of intermediate options exist even before embarking on the brachial artery cephalic vein (at elbow level) fistula, including proximal RCF options described by Toledo‐Pereyra et al, Gracz et al, and Bonforte et al Ulnar‐basilic fistula serves as another autogenous vascular access option with acceptable unassisted survival rates . In a recent systematic review, proximal radial RCFs was found safe and reliable although has not gained popularity and it is not in the NKF/DOQI preference list for vascular access . Thus, one might argue for trying to create one of the above options instead of a SG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation